PENGARUH PROFITABILITAS, SOLVABILITAS, UKURAN PERUSAHAAN, DAN OPINI AUDIT TERHADAP AUDIT REPORT LAG PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2017-2018 - susanto, zaid budi (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2019)
ABSTRACT The research aims to examine the effect of profitability, solvency, company size, and audit opinion on audit report lag. The population of this research is the property and real estate companies listed on the Indonesia Stock Exchange period 2017-2018. With the purposive sampling sample collection method, 40 companies were produced as samples and 78 samples were observed. The data type is secondary data. Data were analyzed using multiple linear regression and processed using IBM SPSS statistics 23. The test used in this study is the t test (partial), f test (simultaneous) and R2 test (coefficient of determination). The results indicated that profitability had a significant effect on audit report lag. While solvency, company size, and audit opinion do not have a significant effect on audit report. Keywords: Audit report lag, profitability, solvability, company size, audit opinion